Informed Consent Dan Sengketa Medis Dalam Instalasi Gawat Darurat (IGD): Tinjauan Etik Dan Hukum - Purawijaya, Handrian; Jollis, Jollis; Aswan, Aswan; Ma’mun Fikri, Ahmad (Syntax Corporation, 2025)
Informed consent is a fundamental aspect of medical practice that ensures patients' rights to receive comprehensive information before granting consent to medical procedures. In the Emergency Department (ED), the implementation of informed consent presents unique challenges due to the urgent nature of patients’ conditions. This article discusses the importance of applying informed consent in the ED, the obstacles encountered, and its relevance to potential medical disputes. The methodology used includes literature review and legal-medical analysis. It was found that in emergency situations, ethical and legal principles permit medical interventions without formal consent, as long as they aim to save the patient’s life. However, clear documentation and effective communication remain essential to prevent legal conflicts.